2011 IEEE Control and System Graduate Research Colloquium 2011
DOI: 10.1109/icsgrc.2011.5991831
|View full text |Cite
|
Sign up to set email alerts
|

Hypovigilance warning system: A review on driver alerting techniques

Abstract: In recent years, driver hypovigilance (drowsiness and inattentiveness) is one of the major causes for road accidents and it leads to severe traumas such as physical injuries, deaths, and economic losses. Several researchers have reported on driver drowsiness detection and only very few works have been reported on detecting the driver hypovigilance. The physiological signals and vision based approaches are mostly used for estimating the driver's hypovigilance. When the physical state of the driver is drowsy or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…There are a vast amount of studies on the inattention detection of drivers or pilots using diverse measures, such as subjective, vehicle-based, behavioral, and physiological measures [ 48 ]. Subjective measures indicate the result of a survey, which is hard to be utilized in a real-time system, and vehicle-based and behavioral measures capture the event that occurred due to an operator’s inattention state.…”
Section: Related Workmentioning
confidence: 99%
“…There are a vast amount of studies on the inattention detection of drivers or pilots using diverse measures, such as subjective, vehicle-based, behavioral, and physiological measures [ 48 ]. Subjective measures indicate the result of a survey, which is hard to be utilized in a real-time system, and vehicle-based and behavioral measures capture the event that occurred due to an operator’s inattention state.…”
Section: Related Workmentioning
confidence: 99%
“…These physiological responses can thus be integrated into predictive models to detect hypovigilance for safety purposes (EuroNCAP, 2017; Schwarz & Fuchs, 2018). Multiple reviews have been published to summarize methods for assessing hypovigilance and other related concepts from multiple perspectives (e.g., Arun et al, 2011; Bafna & Hansen, 2021; Bier et al, 2020; Duffy & Feltman, 2022; Larue et al, 2010; Mogilever et al, 2018; Mohanavelu et al, 2017; Sahayadhas et al, 2012). For instance, Bendak and Rashid (2020) provide a systematic review of the causes of fatigue observed in the aviation industry and the ways to measure it.…”
Section: Introductionmentioning
confidence: 99%
“…The driver monitoring component is paired with an alerting system that presents important updates to the driver, including requests for the driver to take over control of the vehicle. Driver takeovers are more effective when multiple alert modalities are combined, although haptic feedback is often most effective whereas visual feedback is often least effective (7)(8)(9). Regardless of the alerting modality, drivers are generally faster in taking control when they anticipate that the vehicle will be unable to perform, when they are less distracted by secondary tasks, and when they experience lower levels of cognitive load (10)(11)(12).…”
mentioning
confidence: 99%